Effect of Video Based Instruction for Teaching Mathematics in Primary Schools in Ifelodun Local Government Area, Lagos State - Obielodan, Omotayo Olabo; Fakomogbon, Michael Ayodele; Amosa, Abdulganiyu Alasela; Njoagwu, R. N. (NIU Journal of Humanities, 2017)
Mathematics is a core subject, which is confronted with inadequacy in quality and quantity of instructional materials. Video based instruction enhances meaningful and productive learning. Thus, the video instructional package is a possible solution to the problem of inadequacy of instructional materials. Therefore, the main purpose of this study was to investigate the effects of video based instruction in teaching mathematics in primary schools, Lagos State. Specifically, the study investigated the difference between pupilsâ€™ performance taught using video based instruction and their counterparts taught using expository method. A pre-test, post-test quasi-experimental design was adopted for the study. The two sampled schools comprised 40 pupils who were randomly assigned to treatment (20 pupils) and control (20 pupils). The research hypotheses were tested using Analysis of Co-variance (ANCOVA). The findings revealed that at significant level, the value produced F (1, 39) = 17.917, the significance of F, alpha = .000 < 0.05 alpha level of significance. Therefore, hypothesis was rejected. This implies that the significance difference exists between the performance of pupils taught with video based instruction and their counterparts taught using expository method. Also, at 0.05 significant level, the value produced F (1, 39) = 0.280, the significance F, alpha = 0.600 > 0.05.  Therefore, hypothesis two was accepted. This implies that the performance of male and female pupils showed no significant difference when taught using video based instruction. Based on the findings of the study, it was recommended that teachers should teach using video based instruction so as to encourage individualized learning. Also, teacher should put more efforts on equal distribution of attention to both male and female pupils. Keywords: Mathematics, video based instruction, pupils and gender